2020
DOI: 10.3390/microorganisms8020164
|View full text |Cite
|
Sign up to set email alerts
|

Mbov_0503 Encodes a Novel Cytoadhesin that Facilitates Mycoplasma bovis Interaction with Tight Junctions

Abstract: Molecules contributing to microbial cytoadhesion are important virulence factors. In Mycoplasma bovis, a minimal bacterium but an important cattle pathogen, binding to host cells is emerging as a complex process involving a broad range of surface-exposed structures. Here, a new cytoadhesin of M. bovis was identified by producing a collection of individual knock-out mutants and evaluating their binding to embryonic bovine lung cells. The cytoadhesive-properties of this surface-exposed protein, which is encoded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…These laboratory conditions have largely contributed to the understanding of the biology of these minimal bacteria but provided only limited information on the strategies these organisms have evolved to secure their survival in the animal host and get access to essential nutritional resources. In the absence of small animal models, eukaryotic cell cultures as re-emerged as a valuable environment to revisit the minimal cell concept at the light of host-pathogen interactions [30][31][32][33]44]. Our functional genomic study with the genome-reduced pathogen M. bovis revealed that phosphodiesterases involved in cyclic dinucleotides and nanoRNAs degradation are critical for survival under cell culture conditions, while dispensable in axenic medium.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These laboratory conditions have largely contributed to the understanding of the biology of these minimal bacteria but provided only limited information on the strategies these organisms have evolved to secure their survival in the animal host and get access to essential nutritional resources. In the absence of small animal models, eukaryotic cell cultures as re-emerged as a valuable environment to revisit the minimal cell concept at the light of host-pathogen interactions [30][31][32][33]44]. Our functional genomic study with the genome-reduced pathogen M. bovis revealed that phosphodiesterases involved in cyclic dinucleotides and nanoRNAs degradation are critical for survival under cell culture conditions, while dispensable in axenic medium.…”
Section: Discussionmentioning
confidence: 99%
“…DNA constructions and oligonucleotide primers used in the present study are listed in S2 Table. Plasmid pOH/P was used as a backbone for complementation studies [16]. This plasmid was derived from p20-1miniO/T by replacing (i) the tetM region by the pac gene encoding a puromycin N-acetyltransferase [12], and (ii) the replication origin of M. agalactiae by its counterpart in HB0801 [33,51]. The plasmid pCP-T9.386 contains a pOH/P backbone in which the Mbov_0328/0327 coding region was inserted under the control of the M. agalactiae P40 lipoprotein promoter [30].…”
Section: Dna Constructions and Oligonucleotide Primersmentioning
confidence: 99%
See 3 more Smart Citations